Cost-effectiveness of a pragmatic structured education intervention for the prevention of type 2 diabetes: economic evaluation of data from the Let's Prevent Diabetes cluster-randomised controlled trial. Issue 1 (9th January 2017) - Leal, J; Ahrabian, D; Davies, M J; Gray, L J; Khunti, K; Yates, T; Gray, A M
Abstract : Objectives: Prevention of type 2 diabetes mellitus (TD2M) is a priority for healthcare systems. We estimated the cost-effectiveness compared with standard care of a structured education programme (Let's Prevent) targeting lifestyle and behaviour change to prevent progression to T2DM in people with prediabetes. Design: Cost-effectiveness analysis alongside randomised controlled trial. Setting: 44 general practices in Leicestershire, England. Participants: 880 participants with prediabetes randomised to receive either standard care or a 6-hour group structured education programme with follow-up sessions in a primary care setting. Main outcome measure: Incremental cost utility from the UK National Health Service (NHS) perspective. Quality of life and resource use measured from baseline and during the 36 months follow-up using the EuroQoL EQ-5D and 15D instruments and an economic questionnaire. Outcomes measured using quality-adjusted life years (QALYs) and healthcare costs calculated in 2012–2013 prices. Results: After accounting for clustering and missing data, the intervention group was found to have a net gain of 0.046 (95% CI −0.0171 to 0.109) QALYs over 3 years, adjusted for baseline utility, at an additional cost of £168 (95% CI −395 to 732) per patient compared with the standard care group. The incremental cost-effectiveness ratio is £3643/QALY with an 86% probability of being cost-effective at a willingness to pay threshold of £20 000/QALY. Conclusions: The education programme had higher costs and higher quality of life compared with the standard care group. The Let's Prevent programme is very likely to be cost-effective at a willingness to pay threshold of £20 000/QALY gained. Trial registration number: ISRCTN80605705.